Seismic Hazard Calculation Using the Equivalent Magnitude Obtained from Numerical Modelling - Hurtado-Cruz, J; Jarufe-Troncoso, J; Perez-Cortes, S (Elsevier Ltd, 2022)
Numerical modelling is widely used to estimate seismic potential in mines. Several numerical methods, along with different interpretation techniques, allow estimating the seismic potential at different stages of a mine or tunnel construction. However, none of the existing methods considers the magnitude of seismic events as a distribution of values, rather all methods focus on obtaining a single value representative of the seismic conditions for each excavation stage. The objective of this study was to develop a method based on the implicit generation of a synthetic distribution of seismic data and on the results of numerical modelling, providing a means to decompose the modelling results into a statistical distribution of maximum magnitudes. The results of this method provide a statistical distribution of the maximum magnitudes, based on existing plastic modelling results and assumptions about the failure mechanism. This work provides an engineering tool to evaluate the probability of the maximum seismic event. © 2022 Elsevier Ltd